2018
DOI: 10.1007/s11854-018-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Wiener-Wintner double recurrence theorem to polynomials

Abstract: We extend our result on the convergence of double recurrence Wiener-Wintner averages to the case where we have a polynomial exponent. We will show that there exists a single set of full measure for which the averages 1 N N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Since G (i 1 ,...,is) is a subgroup of the torus G s and p 1 , p ′ 1 , p 2 , p ′ 2 are distinct primes, it follows that the group G (i 1 ,...,is) is finite. Furthermore, since G = G (1) G (2) , using Lemma 8.3 and induction, we have that the group G s is the product of the groups G (i 1 ,...,is) for i 1 , . .…”
Section: 33mentioning
confidence: 99%
See 3 more Smart Citations
“…Since G (i 1 ,...,is) is a subgroup of the torus G s and p 1 , p ′ 1 , p 2 , p ′ 2 are distinct primes, it follows that the group G (i 1 ,...,is) is finite. Furthermore, since G = G (1) G (2) , using Lemma 8.3 and induction, we have that the group G s is the product of the groups G (i 1 ,...,is) for i 1 , . .…”
Section: 33mentioning
confidence: 99%
“…(ii) Bounded generalized polynomials (see [48,Corollary 2.23]). 2 These include sequences of the form ({p(n)}) n∈N or (e(p(n))) n∈N , where p : N → Z is an arbitrary generalized polynomial, {x} denotes the fractional part of x, and e(t) := e 2πit .…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Therein, the authors proved a Wiener-Wintner version of BDRT, that is, the exponential sequences (e 2πint ) n∈Z are good weight for the homogeneous ergodic bilinear averages. Subsequently, I. Assani and R. Moore showed that the polynomials exponential sequences e 2πiP (n) n∈Z are also uniformly good weights for the homogeneous ergodic bilinear averages [8]. One year later, I. Assani [9] and P. Zorin-Kranich [28] proved independently that the nilsequences are uniformly good weights for the homogeneous ergodic bilinear averages.…”
Section: Introductionmentioning
confidence: 99%